Combination therapy in cancer: effects of angiogenesis inhibitors on drug pharmacokinetics and pharmacodynamics. Issue 1 (December 2016) - Fuso Nerini, Ilaria; Cesca, Marta; Bizzaro, Francesca; Giavazzi, Raffaella
Abstract Validated preclinical studies have provided evidence that anti-vascular endothelial growth factor (VEGF) compounds enhance the activity of subsequent antitumor therapy, but the mechanism of this potentiation is far from clear. The most widespread explanation is enhanced delivery of therapeutics due to vascular remodeling, lower interstitial pressure, and increased blood flow. While the antiangiogenic effects on vascular morphology have been fairly consistent in both preclinical and clinical settings, the improvement of tumor vessel function is debated. This review focuses on the effect of anti-VEGF therapy on tumor microenvironment morphology and functions, and its therapeutic benefits when combined with other therapies. The uptake and spatial distribution of chemotherapeutic agents into the tumor after anti-VEGF are examined.